Please - Joyce, Melanie; Wood, Hannah (Cottage Farm, England Autumn Publishing, 2017)
When the animals in this story want a tasty treat, they have to say the magic word, but Lamb can't remember what it is! Can you help her remember?
Linguistic Notions
1 13 23
Keywords: Courtesy -- Juvenile fiction; Manners -- Juvenile fiction